Enhanced Fluorescence in a Scattering Medium. Issue 12 (December 2021) - Giauque, Nathan A.; Flowerday, Callum E.; Goates, Steven R.
Often only small amounts of sample are available for spectroscopic analytical determinations. This work investigates the enhancement of signal in columns packed with silica particles. We propose that silica particles cause the light to scatter through the column, effectively increasing optical path length. Packed columns are shown to be effective with fluorescence spectroscopy, but results were inconclusive with absorbance spectroscopy. Graphical Abstract